Photoconductivity and IR Studies of 3-Nitroacetanilide Single Crystal : A Potential Organic Non-linear Optical Material - PARI, S.; RAVICHANDRAN, T.; RAJKUMAR, V.; KUMARARAMAN, S. (Asian Journal of Chemistry, 2010)
3-Nitroacetanilide was grown by slow evaporation technique using acetone as a solvent. In order to calculate the lattice parameter values, powder X-ray diffraction studies were carried out on the grown sample. Various functional groups of the 3-nitroacetanilide was identified by FTIR studies. Photoconductivity of the grown sample was studied.